Neoadjuvant Phase II Trial of Chemoradiotherapy in Patients With Resectable and Borderline Resectable Pancreatic Cancer. (June 2020) - Thanikachalam, Kannan; Damarla, Vijay; Seixas, Trevor; Dobrosotskaya, Irina; Wollner, Ira; Kwon, David; Winters, Kenneth; Raoufi, Mohammad; Li, Jia; Siddiqui, Farzan; Khan, Gazala
Abstract : Background: Pancreatic ductal adenocarcinoma is a largely incurable cancer. Surgical resection remains the only potential option for cure. Even in surgically resectable patients, only about 10% to 20% are long-term survivors. Emerging data suggest a role for neoadjuvant therapy to target occult micrometastatic disease. Aim: To report our institutional experience with a novel neoadjuvant chemoradiation (CRT) regimen in resectable and borderline resectable pancreatic cancer. Materials and Methods: Patients were treated with 2 cycles of induction chemotherapy with FOLFOX and then received CRT with gemcitabine and intensity-modulated radiotherapy (IMRT). Results: From April 2014 to June 2017, 24 patients were enrolled. Eighteen patients were borderline resectable and 6 patients were resectable. All patients received induction chemotherapy with FOLFOX. Thirteen patients underwent pancreatectomy after CRT with a resection rate of 62%. R0 resection achieved in 11 patients (84.6%) and 2 patients had R1 resection (15.4%). For patients who underwent resection, the median progression-free survival (PFS) was 31 months, 1-year PFS rate was 69.2% (95% confidence interval [CI], 0.48-0.99), and 2-year PFS rate was 51.9% (95% CI, 0.3-0.89). Median overall survival (OS) was 34.8 months (95% CI, 1.045 to infinity), 1-year OS rate was 91.7% (95% CI, 0.77-1.0), and 2-year OS rate was 75% (95% CI, 0.54-1.0). Median CA 19-9 at screening for patients who underwent surgery was 659 (range, 18 to 2154), which decreased to 146.9 (range, 18 to 462) after CRT before resection. Conclusion: Neoadjuvant therapy for borderline resectable and resectable pancreatic ductal adenocarcinoma with CRT facilitated R0 resection in 84% patients who underwent surgery.